MENGAKSES INTERNET MENINGKATKAN KINERJA DOSEN - Sofyan, Sofyan (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
Internet as modern mass media present much informations include informations about sciences and technologies. With Internet, each person can changes any informations in his computers file. From year to year.sum of Indonesian Internet users are increasing. Uses and gratification theory, Uses and Effect theory and performance theory can be use in analyses abut correlation between Internet acses and dosen performance.